KECERDASAN EMOSIONAL TOKOH GHOMA DALAM DRAMA AZ-ZA’IM KARYA MUSTHAFA MAHMOUD: KAJIAN PSIKOLOGI DANIEL GOLEMAN - Sayyidah Khoizuroonah; Mukhammad Kamil Pribadi; Bermawy Munthe (Afshaha: Jurnal Bahasa dan Sastra Arab, 2026)
Emotional intelligence plays a crucial role in shaping emotional development and how a person adapts, both in personal contexts and when interacting in social environments. This study focuses on the emotional intelligence of the character Ghoma in the Az-Za’im drama by Musthafa Mahmoud and using Daniel Goleman’s theory of emotional intelligence. The purpose of this study is to reveal the forms of self-awareness, self-regulation, motivation, empathy, and social skills exhibited by the character Ghoma. This study employs a qualitative descriptive method, utilizing data in the form of dialogues or sentences that demonstrate the character Ghoma’s emotional intelligence. The results indicate that the character Ghoma possesses strong and stable emotional intelligence. He exhibits five indicators of self-awareness, five indicators of self-regulation, four indicators of motivation, three indicators of empathy and three indicators of social skills. Ghoma is depicted as capable of recognizing his own emotions, restraining aggressive impulses, managing political tensions, and making strategic decisions that involve moral and collective considerations. Furthermore, he is able to convert emotions into the energy of struggle and maintain social relationships with fellow comrades through persuasive communication. The study’s conclusion indicates that Ghoma’s emotional intelligence serves as the primary foundation of his leadership in confronting colonial conflict and psychological pressure. This research also demonstrates that drama is not merely a representation of social conflict but also a space for the formation of character and the complex emotional dynamics of a people’s leader.